Optimization of fermentation conditions for surfactin produced by Bacillus subtilis G10 - WANG Junfang, ZHANG Piaodan (Zhongguo niangzao, 2024)
In order to improve the production of surfactin, Bacillus subtilis G10, which has the ability to synthesize surfactin, was used as the research object, the surfactin was extracted by acid precipitation and methanol extraction, and its surface activity and antibacterial properties were measured. The fermentation conditions of surfactin synthesized by B. subtilis G10 were optimized by single factor tests and orthogonal tests. The results showed that surfactin had obvious surface activity and antibacterial activity, and the inhibition zone diameters of surfactin against Escherichia coli, Staphylococcus aureus and Saccharomyces cerevisiae were 1.8 cm, 1.9 cm and 1.4 cm, respectively. The optimum fermentation conditions for surfactin synthesis were as follows: rotational speed 200 r/min, fermentation temperature 30 ℃, initial pH 7.5, and the optimal fermentation medium components were glucose 22 g/L, L-Glu 5.0 g/L, MgSO4 0.5 g/L, KCl 0.5 g/L, KH2PO4 1 g/L, FeSO4·7H2O 0.15 g/L, MnSO4 0.65 g/L, CuSO4·5H2O 0.16 g/L. Under these optimized conditions, the average yield of surfactin fermented by B. subtilis G10 was 9.89 g/L, which was 46.7% higher than that before optimization.